DISIPLIN PADA ANAK USIA DINI (Pembiasaan di rumah dan di sekolah) - Ihda A’yunil Khotimah (STPI Bina Insan Mulia Yogyakarta, 2019)
Education is a basic need for every human being which begins with education in the family and then at school, formal, informal and non-formal with different learning characteristics. Education in the family is the main education that will be identified by more children, especially from both parents. Informal learning, namely Kindergarten, is pre-school education that is useful for supporting the stimulation of AUD potential that has been instilled in the family with the principle of fun and enjoy. Discipline behavior is needed by every child so that in the future they can live happily in society because they are used to following the mutually agreed rules. This article is important for parents and educators to know so that children have mental and physical preparation so that they have readiness to face the transition period, namely the transition period. from pre-school education to elementary school education.